Detection of Streptococcus suis using the optimized real-time polymerase chain reaction protocol - Savcheniuk, M. O.; Tarasov, O. A.; Zakharova, O. M.; Korniienko, L. Y.; Zotsenko, V. M.; Tsarenko, T. M. (Regulatory Mechanisms in Biosystems, 2022)
The article presents the results of studies on the detection of Streptococcus suis by real-time polymerase chain reaction. Isolation and species identification of the studied isolates of streptococci was carried out according to morphological, cultural, biochemical and biological properties by conventional methods. The study of cultural characteristics of growth was carried out using conventional bacteriological methods on the brain heart infusion broth (BHI) and BHI agar with the addition of 5% sheep blood (blood BHI agar). To confirm biochemical properties as a confirmatory method, API 20 STREP test kit (bioMerieux, France) was used. In addition, to differentiate S. suis from the non-pathogenic species of streptococci, the hemolysis test was used. As a result of the studies, it was found that the use of the real-time PCR (polymerase chain reaction) method makes it possible to detect S. suis in an amount of 1 x 104 genome copies in the sample. All described validation parameters for the qualitative detection of S. suis DNA by real-time PCR meet international requirements, which guarantees accurate and reliable results. In Ukraine only a diagnostic test kit for convential PCR has been developed for the detection of swine streptococcosis. This approach is more time consuming and complex in comparison with the real-time PCR approach. We recommend that diagnostic laboratories implement this method in their practice. This will increase the number of effective diagnostic tools available to veterinarians on pig farms when they order laboratory tests. The high analytical sensitivity limit of a test is an essential parameter when screening is the focus, and obtaining false negative results causes a risk of the development of infection process among pig populations within infected herds. Our study showed that microbiological diagnostic methods to determine morphological and cultural properties can identify S. suis at the genus level. Determination of biochemical properties using the API 20 STREP test kit can be used to identify S. suis 1 and 2 serotypes. The conventional method and real-time PCR have 100% specificity and can be used to identify S. suis of different serotypes. Real-time PCR is a 2 to 4 times more sensitive limit than conventional PCR depending on the serotype being studied, and can be used to more accurately identify streptococcal DNA. It was found that the use of the real-time PCR method makes it possible to detect S. suis in an amount of 1 x 104 copies of the genome in the sample. Additionally, it was found that all the studied validation parameters of the qualitative method for determining S. suis DNA by real-time PCR meet international requirements, which guarantees accurate and reliable results.